The Status of Glaciers in the Western United States Based on Sentinel-2A Images - Bernard Abubakari; Shrinidhi Ambinakudige (Remote Sensing)
In this study, we utilized Random Forest machine learning classification to assess the current state of glaciers in the western United States using Sentinel-2A satellite imagery. By analyzing Sentinel-2A imagery from September 2020 and comparing it to the RGI inventory, the study determined the current conditions of the glaciers. Our findings unveiled a significant reduction in both glacier area and volume in the western United States since the mid-20th century. Currently, the region hosts 2878 glaciers and perennial snowfield spanning eight states, covering a total area of 428.32 ± 7.8 km2 with a corresponding volume of 9.00 ± 0.9 km3. During the study period, a loss of 244.31 km2 in glacier area was observed, representing a 36.32% decrease when contrasted with the RGI boundaries. The volume lost during this period amounted to 4.96 km3, roughly equivalent to 4.7 gigatons of water. Among the states, Washington experienced the most significant glacier area reduction, with a loss of 133.16 km2. Notably, glaciers in the North Cascade Range of Washington, such as those in Mt. Baker and Mt. Shuksan, now cover, on average, only 85% of their original glacier boundaries with ice and snow at the conclusion of the 2020 hydrological year. Major glaciers, including the White River Glacier, West Nooksack Glacier, and White Chuck Glacier, have lost more than 50 percent of their original area.